2017
DOI: 10.1021/acssuschemeng.7b00193
|View full text |Cite
|
Sign up to set email alerts
|

Organics- and Surfactant-Free Molten Salt Medium Controlled Synthesis of Pt-M (M = Cu and Pd) Bi- and Trimetallic Nanocubes and Nanosheets

Abstract: We present a novel synthetic strategy for the shape-controlled synthesis of Pt-based alloy nanoparticles (NPs) in inorganic molten salt without using any organic surfactants or capping agents. Graphene oxide (GO) was chosen as the stabilizer in the inorganic molten salt synthetic strategy, due to the existence of various oxygen-containing functional groups on its surface, which adsorb, anchor, and stabilize the metal ions or NPs. After GO was added in molten salt, the PtPd nanosheets were formed on its surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 58 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…While the synthesis of intermetallic nanocrystals has been a huge challenge to materials scientists, the reports on intermetallic nanocrystals of Pt 3 Y, Pt 3 Sc, Pt 3 Lu, Pt 2 Na, and Au 2 Y, etc. have demonstrated that the MSS is an effective synthesis approach and should be further explored for them. , …”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…While the synthesis of intermetallic nanocrystals has been a huge challenge to materials scientists, the reports on intermetallic nanocrystals of Pt 3 Y, Pt 3 Sc, Pt 3 Lu, Pt 2 Na, and Au 2 Y, etc. have demonstrated that the MSS is an effective synthesis approach and should be further explored for them. , …”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…have demonstrated that the MSS is an effective synthesis approach and should be further explored for them. 328,329 Molten salts and ionic liquids, which in general are composed of simple ionic pairs and large ionic species and are used in high and low temperature ranges, respectively, seem to be going in opposite directions in the plethora of the syntheses of nanomaterials. 330 It can be a boon to ionic liquid researchers if both empirical and theoretical knowledge of molten salt chemistry can be transferred to them or vice versa.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Metal nanoparticles suspended in molten salt media [1][2][3] can be obtained by reducing their corresponding cations (as halides or oxides) in a mixture with a non-reducible molten salt using hydrogen gas, 4 or an alkali metal. [5][6][7] The reduction potential of alkali metal dissolved in molten alkali halide salts is so large that the alkali atoms ionize to alkali ions and solvated electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Not only that, this method can also effectively control the morphology of the product. Qiu et al [102] added GO to molten salt, used KI as a shape inducer, and synthesized Pt Pd nanocubes with a core-shell structure on the GO surface. The above shows that the melten salt method has a simple synthesis process and a relatively mild reaction temperature, making it easier to realize industrialization.…”
Section: Molten Salt Methodsmentioning
confidence: 99%